The Repeat Sequences and Elevated Substitution Rates of the Chloroplast accD Gene in Cupressophytes - Li, Jia; Su, Yingjuan; Wang, Ting (Frontiers in Plant Science, 2018)
The plastid accD gene encodes a subunit of the acetyl-CoA carboxylase enzyme. The length of accD gene has been supposed to expand in Cryptomeria japonica, Taiwania cryptomerioides, Cephalotaxus, Taxus chinensis, and Podocarpus lambertii, and the main reason for this phenomenon was the existence of tandemly repeated sequences. However, it is still unknown whether the accD gene length in other cupressophytes has expanded. Here, in order to investigate how widespread this phenomenon was, 18 accD sequences and its surrounding regions of cupressophyte were sequenced and analyzed. Together with 39 GenBank sequence data, our taxon sampling covered all the extant gymnosperm orders. The repetitive elements and substitution rates of accD among 57 gymnosperm species were analyzed, the results show: (1) Reading frame length of accD gene in 18 cupressophytes species has also expanded. (2) many repetitive elements were identified in accD gene of cupressophyte lineages. (3) the synonymous and nonsynonymous substitution rates of accD were accelerated in cupressophytes. (4) accD was located in rearrangement endpoints. These results suggested that repetitive elements may mediate the chloroplast genome rearrangement and accelerated the substitution rates.